Do economic, institutional, or political variables explain economic growth - Ahmad, Hasnat; Arif, A.; Mohyudin, S. (Canadian Center of Science and Education, 2012)
This study analyzed the impact of trade openness and institutional variables on GDP growth of Pakistan using annual time series data for the period 1984 to 2010. This study follows the Johansen co-integration analysis and error correction model to analyze the long run relationship among the variables. The result of Johansen co-integration indicates that there exists a long run equilibrium relationship among the variables in the model. There is a negative long-run relationship between real GDP and trade openness. The relationship between government stability (GOV_ST) and real GDP is found to be positive whereas the association between real GDP and corruption is found to be negative. The error correction term (ECT) is statistically significant at the 5% level of significance suggests a moderate speed of convergence to equilibrium.